禅宗心性论与陆王心学的平行研究 (A Parallel Study Between The Chinese Chan Buddhism And The Heart-Mind Philosophy Of Lu-Wang School) - Jia, Shihou (2019)
The mind-nature doctrine of Chinese Chan Buddhism is a theory about the standard guideline of being a Buddha, enlightenment practice and its altruistic teaching. Whereby, the heart-mind philosophy of Lu-Wang school (developed by Lu Xiangshan and Wang Yangming) is a theory about the standards being a saint, saint practice and its altruistic teaching. Both the mind-nature doctrine of Chinese Chan Buddhism and the heart-mind philosophy of Lu-Wang school are respectively summed up in three parts of theory, where, the former comprises the theory of self-nature, the theory of enlightenment practice and the theory of teaching which reflects the three essential elements of becoming a Buddha; the latter comprises the theory of moral, the theory of “gong-fu” and the theory of teaching which reflects the three essential elements of becoming a saint. The former and the latter demonstrate corresponding similarities. This dissertation consists of two primary sections. The first section studies about the establishment and development of the mind-nature doctrine of Chinese Chan Buddhism. This section reveals the employments of literature research, reference material analysis and inductive approach, as well as making references to historical documentations and publications in order to research, analyze and induce what had led to the establishment and development of the mind-nature doctrine of Chinese Chan Buddhism. The establishment of Huineng’s mind-nature doctrine symbolizes the establishment of the mind-nature doctrine of Chinese Chan Buddhism. Pertaining Huineng’s mind-nature doctrine, this study shall be based on the new version of “The Platform Sutra of The Six Patriarch” of Dunhuang, where the study would discuss the three parts of theories of the doctrine which carry the essence about the emergence of the Buddha’s trikāya from self-nature, i.e. the the theory of self-nature elaborates the essence of the Dharmakāya; the theory of enlightenment practice elaborates the essence of IV the Saṃbhogakāya; and, the theory of teaching elaborates the essence of the Nirmāṇakāya. Huineng’s mind-nature doctrine carries the Chinese characteristic emphasizing on the mundane engagement, which is revealed in his concept where lay persons could practice and become a Buddha. This dissertation further investigates and discusses the characteristics of various mind-nature doctrines explicated by other important contributors in the development of the mind-nature doctrine of Chinese Chan Buddhism, namely the founder of Hongzhou school - Mazu Daoyi, the founder of Linji school - Yixuan, the founder of Shitou school – Xiqian and the co-founders of Caodong school - Dongshan and Caoshan. The characteristic of Mazu Daoyi’s explication of the doctrine is: awakening via action, i.e. the actions of mind (speeches and acts) guide practitioners to recognize the mind and see the true nature. Xiqian of Shitou school explicated the doctrine with similar characteristic of awakening via action, however it is about all forms or their actions recognize the mind and lead to enlightenment. The explication by Linji Yixuan is characterized by his particular emphasis on teaching, which he had founded the “Four Kind of Attitudes, Three Mysteries and the Three Essentials, Four Shouts” and contents of other teaching methods, which had further developed to become a characteristic doctrine of non-conceptual which is iconoclastic and eccentric. The co-founders of Caodong school, both Caoshan and Dongshan, had developed the famous methodology of the “Five Positions of Ruler and Minister” and their characteristic doctrine which decries verbal teaching but emphasizes on enlightenment practice. There existed several monks from the school who had demonstrated the ability to pass away in sitting and standing postures; whilst Caoshan and Dongshan both demonstrated the ability to maneuver dying on free will. From these mind-nature doctrines, one reckons that the five Chan masters mentioned above were skillful in using the term “Dao” to depict self-nature, which reflected its integration with Daoism terminology along its development which had helped the mind-nature doctrine of Chinese Chan Buddhism to further advance towards its localization in China. V The second section is about the parallel study comparing the corresponding similarities between the three parts of theories of the mind-nature doctrine of Chinese Chan Buddhism and the three parts of theories of heart-mind philosophy of Lu-Wang school. This section reveals the employments of literature research, reference material analysis, inductive approach, parallel study and references on relevant historical documentations and publications, to study the three parts of theories of the heart-mind philosophy expounded by Lu Xiangshan and Wang Yangming. The parallel study method of the comparative literature is employed here to make analogy and comparison between the three parts of theories of the heart-mind philosophy of Lu-Wang school and the three parts of theories of the mind-nature doctrine of Chinese Chan Buddhism, which consequently reveals that the similarities found in the former is attributed to certain influence by the latter. The former reveals itself as the further development from the latter besides demonstrating its development from its predecessors’ theories in Confucianism. The conclusion of this dissertation is that: enlightenment and practice are mutually inclusive and concurrent, it is the basic characteristic of the mind-nature doctrine of Chinese Chan Buddhism, which belongs to the tathāgatagarbha doctrine of Mahayana tradition, which shows similarities with the tathāgatagarbha concept found in the four-roll Lankāvatāra Sūtra, but the tathāgatagarbha nature of the former refers to the emptiness of self-nature, whereas the tathāgatagarbha nature of the latter refers to the purity of self-nature. Therefore, the former carries the ultimate truth about tathāgatagarbha while signifying further development of the latter. The similarities between the mind-nature doctrines of Chinese Chan Buddhism and the heart-mind philosophy of Lu-Wang school are disclosed in three aspects i.e. the theory of self-nature immanent in the mind-nature doctrine of Chinese Chan Buddhism matches well with the theory of moral of the heart-mind philosophy of Lu-Wang school; whereby, the theory of enlightenment practice of the mind-nature doctrines of Chinese Chan Buddhism shows corresponding consistency with the theory of gong-fu of the heart-mind philosophy of Lu-Wang VI school; lastly, the theory of teaching of the mind-nature doctrine of Chinese Chan Buddhism is similar to the theory of teaching of the heart-mind philosophy of Lu-Wang school. The difference between the mind-nature doctrine of Chinese Chan Buddhism and the heart-mind philosophy of the Lu-Wang school is that the mind-nature doctrine was originated from Buddhism, where its ultimate value is to become a Buddha, who transcends the mundane world; whereby, the heart-mind philosophy of Lu-Wang school was originated from Confucianism with its ultimate value to become a saint engaging in the mundane world. Therefore, albeit some corresponding similarities, both schools carry different ultimate values, which essentially are two different doctrines with different contents which should not be confused and mixed up. The novelty of this dissertation lies in employing the parallel study method of the comparative literature and to make analogy and comparison upon the three parts of theories of the mind-nature doctrine of Chinese Chan Buddhism and the three parts of theories of the heart-mind philosophy of Lu-Wang school, and consequently discover their similarities and differences.